Effects of tACS Combined with Electroacupuncture on Patients with Attention Deficit after Stroke - GUO Qingjuan; WU Jiali; ZHANG Jingjing; ZHANG Guohui; ZHANG Sicong; XUE Xiayan; SHAN Chunlei (康复学报)
ObjectiveTo explore the effect of transcranial alternating current stimulation (tACS) combined with electroacupuncture on the attention function and walking ability of patients with attention deficit after stroke.MethodsA total of 60 patients with attention deficit after stroke treated in the Department of Rehabilitation Medicine in Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, were selected from January to December 2023. The random number table was generated using SPSS26. 0 statistical software to divide it into the control group and the study group, with 30 cases in each group. One case in the control group voluntarily withdrew from the trial; One case in the study group was discharged from the hospital early and fell off automatically, and finally 29 cases were included in each group. The control group received tACS treatment and sham EA stimulation. The tACS treatment frequency was 6Hz, the current was 1mA, and the intervention time was 20 minutes per time. The sham EA stimulation was used to select Shenting and Baihui acupoints. The acupuncture needle could only stimulate the epidermis, did not penetrate the skin, and no current passed through, and the stimulation time was 20 minutes per time. The observation group received tACS treatment and EA stimulation, among which the tACS treatment was the same as the control group; EA stimulation was selected at Shenting and Baihui acupoints, and the acupuncture needle was inserted at 30° to the scalp. The electroacupuncture used sparse and dense waves with a frequency of 2/10Hz. The current intensity was tolerated by the subject, and the intervention time was 20 minutes per time. Both groups were treated once a day and 5 times a week for 2 weeks. The cognitive function was evaluated before and after treatment. The attention function was evaluated by MoCA attention score, trail making test A (TMT-A), and trail making test B (TMT-B). The walking ability score (FAC), hip joint mobility and knee joint mobility were used to evaluate the patient's walking ability, and the correlation analysis was conducted on the walking ability difference and the cognitive attention function difference.Results(1) MoCA total score and attention function score：Compared with before treatment, the MoCA score and MoCA attention score increased significantly in both groups after treatment (P<0.05), and the TMT-A score and TMT-B score decreased significantly (P<0.05). Compared with the control group, the MoCA score and MoCA attention score in the observation group were significantly higher after treatment, and the TMT-B score was significantly lower (P<0.05). (2) FAC score and hip/knee range of motion：Compared with before treatment, the FAC score, hip range of motion, and knee range of motion increased significantly in both groups after treatment (P<0.05). Compared with the control group, the FAC score and hip joint motion after treatment in the observation group were significantly higher (P<0.05), and there was no statistical significance in knee joint motion (P>0.05). (3) Correlation between walking ability difference and cognitive attention difference：There is a positive correlation between FAC difference and MoCA score difference (r=0.333, P<0.05), which was positively correlated with the difference in MoCA attention score (r=0.308, P<0.05); the difference in hip motion was positively correlated with the difference in MoCA score (r=0.425, P<0.05), with the difference in MoCA attention score (r=0.442, P<0.05), and with the difference in TMT-A score (r=0.2931, P<0.05).ConclusiontACS combined with EA can improve the attention function and walking ability of stroke patients with attention deficit. The improvement of walking ability is closely related to cognition and attention function.